PISA for Development: how the OECD and World Bank shaped education governance post-2015. Issue 2 (3rd April 2019) - Auld, Euan; Rappleye, Jeremy; Morris, Paul
ABSTRACT: The year 2015 was significant for the arena of international development, as UNESCO's Education for All agenda was replaced by Education 2030, which would identify minimum standards of education quality. The OECD had been working on extending its existing PISA assessment into low- and middle-income countries through PISA for Development (PISA-D) and positioned the new assessment as a means of tracking progress on the post-2015 goals. The organisation maintains that PISA-D was introduced primarily in response to the demands of the international community, especially low- and middle-income countries, and that the assessment was developed in partnership with them. This paper investigates those claims through an analysis of the arrival of PISA-D in Cambodia, situating the analysis within UNESCO's shifting agenda and the strategic visions of the OECD and World Bank that first emerged in the 1990s. The result is a very different picture to the portrayals of local agency, demand, consensus and partnership that adorn the official websites and pamphlets of global agencies and much academic research, raising serious doubts about education governance post-2015.